Proteomic evaluation of the effect of antifungal agents on Aspergillus westerdijkiae ochratoxin A production in a dry-cured fermented sausage-based medium - Álvarez, Micaela (2022)
Aspergillus westerdijkiae may produce large amounts of ochratoxin A (OTA) in dry-cured meat products. Natural strategies to control ochratoxigenic moulds using biocontrol agents (BCAs) are currently in the spotlight. The aim of this study was to test the effects of Debaryomyces hansenii and its combination with rosemary derivatives and with a commercial antifungal preparation composed by natamycin and potassium sorbate (AP) against A. westerdijkiae in a dry-cured fermented sausage based-medium. The yeast and rosemary leaves were added to the medium, and rosemary essential oil and AP were added on the casings put on the medium surface to simulate the real product. The growth rate, OTA production and comparative proteomics were analysed. The mould growth in the presence of each treatment was not indicative of their efficiency on OTA repression. The treatment with AP did not affect to the OTA concentration, maybe as consequence of the stressful stimulation of the subinhibitory doses used. D. hansenii added alone or with rosemary showed the best results, decreasing the OTA production >80 %, suggesting that it can be useful as preservative agent during industrial processing. Attending to the proteomic results, its antifungal activity seems to be based on the reduction in abundance of proteins involved in OTA biosynthesis and in the cell wall integrity pathway.